2022
DOI: 10.1186/s12913-022-08712-w
|View full text |Cite
|
Sign up to set email alerts
|

Availability of comprehensive emergency obstetric and neonatal care in developing regions in Ethiopia: lessons learned from the USAID transform health activity

Abstract: Background In collaboration with its partners, the Ethiopian government has been implementing standard Emergency Obstetric and Neonatal Care Services (CEmONC) since 2010. However, limited studies documented the lessons learned from such programs on the availability of CEmONC signal functions. This study investigated the availability of CEmONC signal functions and described lessons learned from Transform Health support in Developing Regional State in Ethiopia. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…The difference might be due to the study period. This study also showed that 66% of hospitals performed blood transfusions which was comparable with the study finding in Ethiopian developing regions, 66.6% [ 27 ]. Whereas the finding of this study was lower than the national Ethiopian service availability and readiness report 82% [ 21 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The difference might be due to the study period. This study also showed that 66% of hospitals performed blood transfusions which was comparable with the study finding in Ethiopian developing regions, 66.6% [ 27 ]. Whereas the finding of this study was lower than the national Ethiopian service availability and readiness report 82% [ 21 ].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, cesarean section was performed in 50% of hospitals, which was lower than the national Ethiopian service availability and readiness report of 86% [ 21 ] and study finding in Ethiopian developing regions [ 27 ]. The difference might be due to the study period.…”
Section: Discussionmentioning
confidence: 69%
“…After the training was initially planned, however, it had to be radically revised in order to adapt to the limitations created by the onset of the global COVID-19 pandemic in 2020. The most obvious challenge was that the Swiss partners could not travel to Madagascar to deliver the training [ 1 , 17 , 25 , 26 ]. Other challenges included changing institutional priorities among the partners (as they pivoted to addressing COVID-19) and COVID-19-related supply chain interruptions [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…EmONC services are a set of key obstetric services or signal functions provided for pregnant women and newborns against fatal complications, such as bleeding, infection, prolonged or obstructed labor, eclampsia, and asphyxia. 1,5 Emergency care is recognized as an essential and effective component of obstetric services. 6,7 Since 2008, the Ethiopian government has been providing standard EmONC in all health facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Emergency obstetric and newborn care (EmONC; basic versus comprehensive) refers to caring for women and newborns during pregnancy, delivery, and postpartum to prevent serious complications or death. [1][2][3][4] The World Health Organization (WHO) estimates that, globally, approximately 15% of expected births develop life-threatening complications during pregnancy, delivery, or at the Maternal satisfaction with emergency obstetric and newborn care services in Ethiopia and the associated factors: A systematic review and meta-analysis postpartum period. EmONC services are a set of key obstetric services or signal functions provided for pregnant women and newborns against fatal complications, such as bleeding, infection, prolonged or obstructed labor, eclampsia, and asphyxia.…”
Section: Introductionmentioning
confidence: 99%